O papel das políticas públicas no desenvolvimento da região das cidades gêmeas de Foz do Iguaçu, Ciudad del Este e Puerto Iguazú - Avelar, João Marcos Borges (2018)
The transboundary region of the Twin Cities (Cidades Gêmeas) consists of the areas located along the line separating the cities/territories of Foz do Iguaçu/ Brazil, Puerto Iguazú/Argentina and Ciudad del Este/Paraguay, respectively, being, nowadays, a center of great commercial flow and a touristic potential region. The objective of the research is to analyze how the Brazilian public policies developed in the Transboundary Region of the Twin Cities were perceived by the three cities and provided the opportunity to form an integrated development project. During the cited period, Brazilian government implemented relevant public policies for border areas, some of them carried out in the region under study. Concerning to Brazilian side, the research data indicate that, although those policies have occurred during a considerable socioeconomic development period of Foz do Iguaçu city, there is no sufficient evidence to considerate such policies as a result of their implementation. Moreover, there is a lack of statistical data related to the other cities involved in the study to undertake a comparative analysis. It can be said that there is an effective work of the economic and social developmental councils of each city, in an attempt to consolidate an integrated development Project. However, the results obtained until now are poor and not so relevant and the reflexes of Brazilian public policies have not been enough yet to affirm that they contribute significantly for the socioeconomic development of Ciudad del Este and Puerto Iguazú. On the other hand, the data point out that Itaipu Technological Park (PTI) is one of the main developmental agents in the regionand that local governance can make a significant contribution to promoting joint actions between the three cities.